HUBUNGAN PERILAKU ASERTIF DENGAN HASIL BELAJAR FIQIH SISWA KELAS X MADRASAH ALIYAH AL-ISLAM JAMSAREN SURAKARTA - Hanifah Hanifah; Ngatmin Abbas; Sugiyat Sugiyat (STKIP Pesisir Selatan, 2025)
This study aims to determine the relationship between assertive behavior and learning outcomes in the Fiqh subject among tenth-grade students at MA Al-Islam Jamsaren, Surakarta. A quantitative correlational approach was used, involving the entire population (66 students) as the sample. Assertive behavior was measured using a validated questionnaire, while Fiqh learning outcomes were obtained from semester report card scores. Data analysis included descriptive statistics, prerequisite tests (normality and linearity), and hypothesis testing with Pearson correlation. The results indicate that students’ assertive behavior is in the moderate category, with an average score of 125.03. The average Fiqh score is 79.83 (classified as good), with class X-1 having the highest mean (80.41). Pearson correlation testing yielded r = -0.315 with p = 0.010 (< 0.05), indicating a significant but weak relationship between assertive behavior and Fiqh learning outcomes. The relationship is negative, meaning higher assertiveness tends to be associated with slightly lower learning outcomes, although the correlation is relatively weak. These findings imply that students’ assertive behavior plays a role in the learning process, but its impact on Fiqh academic achievement is not strong. Teachers and schools are advised to continue fostering assertiveness through active learning strategies while also addressing other factors that may affect learning outcomes.